Ball trajectories and the probability of scoring a goal in elite male goalball throws - Rafael Fujita; Otávio Furtado; Márcio Morato (European Federation of Adapted Physical Activity, 2021)
Goalball court can be divided into six sectors, each measuring 1.5m in width. The sectors are used for analysing the game. To shed light on spatial factors that may influence offensive and defensive success in goalball, we analysed the throwing frequency and attack efficacy with different ball trajectories in elite male goalball attacks. We determined the origin and target sectors (sector 1 on the far-right goalpost of the court and sector 6 to the left goalpost to goalpost) of 7949 throws from 49 matches played at Paralympic Games and World Championships. The reliability ranged from .82 to 1.00 using the Kappa index. Our findings showed that attackers frequently used the side sectors as the origin and threw the majority of balls at either the target sectors in front of them or the direct neighbour sectors, justifying a team's defensive movement as a block towards the opponent's attack origin. Throw trajectory efficacy originating from sector 2 (the second far-right of the goalpost) was not equally distributed among the different target sectors. In particular, balls directed to sector 3 presented an overall higher likelihood of success (5.4%). Additionally, ball trajectory efficacy from sector 1 to 3 was statistically different between winners vs. losers (5.4% vs. 0.5%, p = .02) and best vs. worst teams 9.4% vs. 2.2%, p = .02). This knowledge has the potential to help goalball coaches to structure specific offensive and defensive training programs.